Dequeísmo and queísmo in the students of the Faculty of Letters and Human Sciences of the Universidad Nacional Mayor de San Marcos of Lima-Peru - Robles-Muñoz, Mirella (2023)
Studies of queísmo and dequeísmo record evidence of these forms in higher education contexts; that is, in environments where it is assumed that the use of the standard language predominates. Along these lines, research has been carried out in spaces such as universities. These phenomena, which correspond to non-standard uses, are even used by students of Humanities or Literature. The objective of this research is to describe the extended use of these linguistic forms in students of the Faculty of Letters and Human Sciences (FLCH) of the Universidad Nacional Mayor de San Marcos (UNMSM) in Lima-Peru, using two academic variables: courses in the university academic specialty and time in the university academic specialty. Methodologically, 40 students from FLCH schools were surveyed. This sample comprises students who entered to study between the years 2016 and 2020. The results of the work show that these language phenomena are evidenced in a formal context, as is the FLCH of the UNMSM, with greater occurrence in queísmo and that the variable courses in the university academic specialty is the most influential.